Toward Strategic Intelligence Systems - Montgomery, David B. (Institutional Knowledge at Singapore Management University, 1979)
The use of strategic planning tools has increased dramatically in the past 10 years. Since the quality of strategic planning will be greatly impacted by the quality of the information inputs, increasing attention needs to be given to the systematic development of strategic intelligence systems. A strategic plan can be no better than the information on which it is based; however, this critical point is often disregarded.As more organizations implement strategic planning and management activities, an increasing need for strategic intelligence systems (SIS) becomes apparent. SIS assists managers in learning about the important environments with which their organization interrelates and in becoming aware of threats and opportunities that are posed. The construction of viable SIS is very complex because of the unstructured nature of strategic decisions, the difficulty of separating important and relevant information from the vast amounts of data accessible to the manager, and the dependence of managers on personal information sources. For a strategic intelligence system to be useful, a firm must have a commitment to strategic planning.